Construction de la Coopération Inter-Organisationnelle Des Organisations de l’Economie Sociale et Solidaire - Affaghrou, Wafa; Ahrouch , Said (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
The practice of inter-organizational coopération is widely appreciated by companies seeking to improve their competitiveness and the acquisition of important competitive advantages. For Social and Solidarity Economy Organizations, the main objective of cooperation is to enhance their complementarity, while maintaining their autonomy and social values. Yet cooperation within this sector is based on common social interest and trust rather than formal agreement. Through this paper, we propose a conceptual model of the cooperation of the Social and Solidarity Economy Organizations, allowing to expose the nature of the relations and their influence on the economic and social development of the cooperating members. Three theories are mobilized to build this model: the theory of transaction costs, the theory of trust and game theory.